Magnetic resonance imaging (MRI) and dynamic MRI evaluation of extranodal non-hodgkin lymphoma in the oral and maxillofacial regions. A systematic review. - Paul, Sebastin Varghese; G. D, Dr. Dharanidharan; Shunmugavelu, Karthik (Student's Journal of Health Research Africa, 2025)
Background: Extranodal non-Hodgkin lymphoma (NHL) in the oral and maxillofacial region often mimics squamous cell carcinoma (SCC), complicating diagnosis. Magnetic resonance imaging (MRI) and dynamic contrast-enhanced MRI (DCE-MRI) offer detailed soft-tissue and functional assessment. This review evaluated their role in identifying characteristic imaging features of extranodal NHL. Methods: Conducted per PRISMA 2020 and registered in PROSPERO (CRD420251178334), a comprehensive search of PubMed, Scopus, Web of Science, and Google Scholar (up to 2025) was performed. Studies on histopathologically confirmed extranodal NHL assessed using MRI or DCE-MRI were included. Data on imaging features, apparent diffusion coefficient (ADC), enhancement kinetics, and diagnostic performance were extracted. Study quality was evaluated using QUADAS-2, and findings were synthesized qualitatively. Results: Seven studies (2004–2018) involving ~250 patients were included. NHL typically showed intermediate-to-low T1 and intermediate-to-high T2 signal intensity, homogeneous contrast enhancement, and submucosal spread with preserved mucosa. DCE-MRI demonstrated a Type II (plateau) enhancement curve, while diffusion-weighted imaging revealed low ADC values (0.68–0.90 × 10⁻³ mm²/s), consistent with high cellularity. SCC showed heterogeneous enhancement, necrosis, and higher ADC values. Combined DWI and DCE-MRI achieved diagnostic accuracies >90%, with sensitivities of 92–96% and specificities of 88–93%. Conclusion: Extranodal NHL exhibits consistent MRI characteristics correlating with histopathology. Multiparametric MRI aids pre-biopsy differentiation from carcinoma and supports treatment planning. Standardized imaging protocols and validated ADC thresholds are needed to improve diagnostic precision.